Native RNA Purification Method for Small RNA Molecules Based on Asymmetrical Flow Field-Flow Fractionation - Levanova Alesia A; Lampi Mirka; Kalke Kiira; Hukkanen Veijo; Poranen Minna M; Eskelin Katri (MDPI, 2022)
RNA molecules provide promising new possibilities for the prevention and treatment of viral infections and diseases. The rapid development of RNA biology and medicine requires advanced methods for the purification of RNA molecules, which allow fast and efficient RNA processing, preferably under non-denaturing conditions. Asymmetrical flow field-flow fractionation (AF4) enables gentle separation and purification of macromolecules based on their diffusion coefficients. The aim of the study was to develop an AF4 method for efficient purification of enzymatically produced antiviral small interfering (si)RNA molecules and to evaluate the overall potential of AF4 in the separation of short single-stranded (ss) and double-stranded (ds) RNA molecules. We show that AF4 separates monomeric ssRNA from dsRNA molecules of the same size and monomeric ssRNA from multimeric forms of the same ssRNA. The developed AF4 method enabled the separation of enzymatically produced 27-nt siRNAs from partially digested substrate dsRNA, which is potentially toxic for mammalian cells. The recovery of AF4-purified enzymatically produced siRNA molecules was about 70%, which is about 20% higher than obtained using anion-exchange chromatography. The AF4-purified siRNAs were not toxic for mammalian cells and fully retained their biological activity as confirmed by efficient inhibition of herpes simplex virus 1 replication in cell culture. Our work is the first to develop AF4 methods for the separation of short RNA molecules.